A model of developing mathematics teachers to enhance the use of TPACK, PBL, CBL, and CLIL integrated learning - Poonputta, Apantee; Intasena, Autthapon; Worapun, Wittaya (International Journal of Innovative Research and Scientific Studies, 2025)
The purposes of this study were to design a model for developing learning management skills in TPACK, PBL, CBL, and CLIL integrated learning, and to implement this model with mathematics teachers. The research was conducted in two phases: the first phase involved a focus group discussion among nine scholars to develop the model and design activities that integrate these principles into mathematics instruction. The second phase focused on implementing the model with 20 volunteer mathematics teachers from northeastern Thailand. The instruments included a problem analysis questionnaire, self-assessment forms, teaching skills evaluation rubrics, and a satisfaction questionnaire. Data were analyzed using mean scores, standard deviations, percentages, and a one-sample t-test, with an 80% criterion set for success. The results indicated that the model effectively enhanced teachers' learning management skills, increased their confidence, and led to high levels of satisfaction. This study contributes a practical and effective approach for integrating TPACK, PBL, CBL, and CLIL into mathematics education, offering a valuable framework for teacher development programs.